2014
DOI: 10.1016/j.addbeh.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

When you see it, let it be: Urgency, mindfulness and adolescent substance use

Abstract: The emotion-based domains of impulsivity, positive and negative urgency, are facets that have garnered attention due to their associations with substance use, and mindfulness based strategies have shown promise in reducing substance use in adults. The aim of the current study was to examine relations among urgency, mindfulness, and substance use in adolescence. Cross-sectional data were collected from students (N = 1,051) at a large, private high school in the Pacific Northwest. Both positive and negative urge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
(30 reference statements)
3
26
0
4
Order By: Relevance
“…Recently, colleagues (2015, 2016) were able to replicate the protective effect of alcohol PBS use on alcohol outcomes, as well as most of the direct effects of antecedent variables on alcohol PBS use, including age at drinking onset (positive), drinking motives (negative), and impulsivity-like traits 2 (negative; Bravo et al, 2015Bravo et al, , 2016. Similar to what has been found in the alcohol field, male sex (Johnston et al, 2015), earlier age at first use (Chen et al, 2009), impulsivity-like traits (Kaiser et al, 2012;Robinson et al, 2014;Wardell et al, 2016), and marijuana use motives (Simons et al, 1998;Zvolensky et al, 2007) have all been shown to be risk factors associated with increased marijuana use, consequences, and/or dependence. However, given the nascence of the marijuana PBS field, no studies have examined whether marijuana PBS use mediates the associations between these antecedents and marijuana-related outcomes.…”
supporting
confidence: 63%
“…Recently, colleagues (2015, 2016) were able to replicate the protective effect of alcohol PBS use on alcohol outcomes, as well as most of the direct effects of antecedent variables on alcohol PBS use, including age at drinking onset (positive), drinking motives (negative), and impulsivity-like traits 2 (negative; Bravo et al, 2015Bravo et al, , 2016. Similar to what has been found in the alcohol field, male sex (Johnston et al, 2015), earlier age at first use (Chen et al, 2009), impulsivity-like traits (Kaiser et al, 2012;Robinson et al, 2014;Wardell et al, 2016), and marijuana use motives (Simons et al, 1998;Zvolensky et al, 2007) have all been shown to be risk factors associated with increased marijuana use, consequences, and/or dependence. However, given the nascence of the marijuana PBS field, no studies have examined whether marijuana PBS use mediates the associations between these antecedents and marijuana-related outcomes.…”
supporting
confidence: 63%
“…Positive and negative urgency show the most robust relationship with the risk for SUDs and drug-related problems. In adolescents, positive and negative urgency were positively associated with problematic alcohol use (Settles et al, 2012; Stautz & Cooper, 2014; Tomko et al, 2016; Wardell et al, 2016; Wolitzky-Taylor et al, 2016) and marijuana use (Robinson, Ladd, & Anderson, 2014; Stautz & Cooper, 2014; Wardell et al, 2016). Further, positive urgency was related to drug use (Stautz & Cooper, 2013), and negative urgency was related to problematic cannabis use (Wardell et al, 2016; Wolitzky-Taylor et al, 2016).…”
Section: Review Of Impulsive Behavior and Drug Use In Adolescence mentioning
confidence: 99%
“…There is preliminary evidence that negative urgency is associated with marijuana use (e.g., Pang et al, 2014;Robinson et al, 2014) and negative marijuana consequences (e.g., Churchwell et al, 2010). Lack of planning has been robustly associated with adolescent marijuana use and frequency in some studies (e.g., Xiao, 2008;Castellanos-Ryan et al, 2013) but unrelated in other studies (e.g., Kong et al, 2013;Leeman et al, 2014).…”
Section: Separable Impulsivity Traits: the Upps-p Modelmentioning
confidence: 99%